Autophagic vacuolar myopathy involving the phenotype of spinocerebellar ataxia type 3. Issue 2 (17th August 2022) - Li, Jingjing; Peng, Yun; Tang, Jincai; Li, Menghua; Zhu, Min; Zhou, Meihong; Fang, Pu; Hong, Daojun
Abstract : Spinocerebellar ataxia type 3 (SCA3) is a form of autosomal dominant cerebellar ataxia with a wide range of clinical manifestations, including ataxia and pyramidal and extrapyramidal signs. A few SCA3 patients have been noticed to be predisposed to the development of inclusion body myositis. It is still unknown whether muscle can be primarily involved in the pathogenesis of SCA3. This study reported an SCA3 family in which the index patient initially presented with parkinsonism, sensory ataxia, and distal myopathy but the absence of cerebellar and pyramidal symptoms. The clinical and electrophysiological studies implied a possible combination of distal myopathy and sensory–motor neuropathy or neuronopathy. MRI muscle showed selective fat infiltration and absence of denervated edema‐like changes, indicating the distal muscle weakness had a myopathic origin. Muscle pathology showed the myopathic involvement, besides neurogenic involvement, characterized by chronic myopathic changes with multiple autophagic vacuoles. Genetic screening revealed expanded CAG of 61 repeats in the ATXN3 gene, which showed co‐segregation in the family. Besides the neurogenic origin, the myopathic origin may be partly attributed to the limb weakness of SCA3 patients, which expands the spectrum of the clinical manifestation of SCA3.